Initiation of Diabetes Treatment: Variations from Current Guidelines - Ashrafuzzaman, SM; Mir, Ahmed Salam; Latif, Zafar Ahmed (BIRDEM Medical Journal, 2017)
Background: Bangladesh is a developing country with a population of 160 million, diabetes prevalence of 6- 10% and 85-90% being type 2. Most diabetic patients receive treatment by general practitioners because of scarcity of Endocrinologist and Diabetologists. But, by most of them, initiation of diabetes treatment along with lifestyle is not always in accordance to any guideline proposed by ADA, EASD, AACE, IDF, WHO etc. The current study was designed to find out the practice of follower of Diabetes Guidelines. Methods:From January to December 2014, 1745 prescriptions for newly detected type 2 diabetes were recorded. Their age and BMI, FPG, 2-h PG and HbA1c were recorded. Results: Mean age was 42±12 years and mean BMI was 25±4.2 Kg/m2. Mean FPG 9.4±1.2 mmol/L and 2-h PG 17.7 ±3.4 mmol/L and mean HbA1c was (done in 235 subjects) 9.1±1.3%. Along with lifestyle, metformin (Met) alone (9%), sulfonylurea (SU) alone (8%), Met+SU(41%), Met+DPPIVi(22%), Met plus insulin (7%) were prescribed. Lifestyle alone (6%) and 3 drugs together (insulin, Met, SU/DPP IVi) (7%) were also prescribed. Many of the prescriptions were not in accordance with established guidelines. Conclusion: Current survey concludes that the well accepted guidelines are not properly followed in many newly detected type 2 diabetic subjects. However, every patient is different, so, every aspects of a patient including co-morbidities should be taken in to account before prescribing, still physicians should be aware of existence of guidelines and their utility. Birdem Med J 2016; 6(2): 91-94